A roadmap toward implementing health technology assessment in Egypt - Fasseeh, Ahmad Nader; Elezbawy, Baher; Gamal, Mary; Seyam, Ahmed; Abourawash, Asmaa; George, Mohsen; Anwar, Mohamed; Amin, Magdy; Khalifa, Ahmed Yehia; Elshalakani, Amr; Hatem, Ashraf; Abdelhamid, Sohir; et al. (Frontiers in Public Health, 2022)
Background The Egyptian healthcare system is currently in the early phase of health technology assessment (HTA) implementation. The aim of this study is to propose an implementation roadmap based on the national healthcare system status. Methods A survey was conducted among Egyptian healthcare sector decision-makers to assess the current and future (preferred) HTA implementation status in Egypt based on a widely used international scorecard methodology. Subsequently, interviews were conducted with experts representing middle- and top-tier management in the Egyptian healthcare system to interpret the survey results and recommend specific actions. Results Experts recommended more capacity-building programs for HTA and health economics. Additionally, they proposed establishing HTA units in separate healthcare authorities and merging them into a single central HTA unit in the long term. Regarding the scope of implementation, experts recommended commencing with the assessment of innovative pharmaceuticals, and thereafter, expanding the scope to cover all health technologies in the long term. Additionally, they recommended using innovative tools such as “multi-criteria decision analysis (MCDA)” for tendering, and “managed entry agreements” for reimbursement decisions. Local burden of diseases and costing studies were also recommended to facilitate the implementation of HTA. Conclusion Experts agreed that several actions are required for successful HTA implementation in Egypt, including coordination between HTA bodies, application of an explicit MCDA framework, and strengthening of local evidence generation. To implement these actions, investment in technical capacity-building is indispensable. Most experts favored using multiple and soft cost-effectiveness thresholds. Efforts should be made to publish HTA submission guidelines and timelines of the processes.